Targeting subsidies through output-based aid - Mumssen, Yogita (World Bank, Washington, DC, 2012)
Output-based aid (OBA), or performance-based grants, can be used to help target services to the poor. Under OBA schemes, service providers are compensated only after delivery of a specified output, such as water connections of a specified quality, to a targeted beneficiary. In most cases that targeted beneficiary would be a poor household or community. Subsidies are provided in the form of payments for the provision of service to targeted groups to help cover the gap between the cost of provision and the user's ability to pay. Targeting subsidies involves challenges. OBA can provide opportunities to enhance targeting and lead to greater transparency in reaching the poor. While OBA is not yet mainstreamed in all infrastructure and social services sectors, the principles and mechanisms are compelling, and initial results promising.